Akuntabilitas, Transparansi, Partisipasi Masyarakat dan Efektivitas Pengelolaan Dana Desa - Ahmad, Rofi; Susilawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Village funds are a concrete form of state recognition of the rights of origin of villages and village communities. It is hoped that this village fund will be able to provide additional village energy to encourage village development and strengthen villages that are stronger, more progressive and independent. Village funds themselves began to be implemented in 2015 after the publication of Law Number 6 of 2014 concerning Villages and Government Regulation Number 6 of 2014 concerning village funds sourced from the APBN. The problems that occurred in several villages in Bandung district showed indications of problems in managing village funds, where in terms of accountability, delays were found and village government financial reports had not been submitted. Apart from that, there have been acts detrimental to the state, such as misappropriation of village funds. This research aims to analyze the influence of accountability, transparency and community participation on the effectiveness of village fund management in Bandung district. This research was conducted using a quantitative approach with a sample of 73 villages in Bandung Regency. Primary data was obtained through distributing questionnaires. This research uses multiple linear regression analysis. The research results show that accountability, transparency and community participation simultaneously have a significant effect on the effectiveness of village fund management. This means that more higher the accountability, more higher the transparency and more higher the community participation, the more effective the management of Village funds will be.